Two case of bilateral approach in laparoscopic pancreas-sparing distal duodenectomy for duodenal neoplasms arising from the distal duodenum. (March 2021) - Nagano, Hideki; Yoshimura, Fumihiro; Shimaoka, Hideki; Maki, Kenji; Yoshimatsu, Gumpei; Hasegawa, Suguru
Highlights: Surgical procedures for duodenal tumors at third and fourth portion of duodenum. The procedures do not require either Kocher's maneuver and Cattell–Braasch maneuver. Preferable approach for laparoscopic pancreas sparing distal duodenectomy. Pancreas was safely preserved during the procedures. Abstract: Introduction: Laparoscopic pancreas-sparing distal duodenectomy is a less invasive surgical therapy; however, the anatomical complexity of the duodenum increases the difficulty of laparoscopic procedures. We introduce our technique for laparoscopic pancreas-sparing distal duodenectomy for distal duodenal tumors. Presentation of cases: A first patient was 47-year-old woman who had 30 mm of duodenal tumor which located in third portion of duodenum. A second patient was 66-year-old man who had 35 mm of submucosal tumor which located in the third portion of duodenum. Laparoscopic pancreas-sparing duodenectomy was performed using bilateral approach for both cases. We began by dissecting an avascular area on the right side of the transverse mesocolon to mobilize the second and third portions of the duodenum with the uncinate process of the pancreas. Next, from the left side, the jejunum and the fourth portion of the duodenum were fully mobilized orally from the surrounding tissue, connecting the dissection plane with the right-side area. The jejunum and duodenum were cut with a linear stapler. Intracorporeal reconstruction was performed in an overlapped manner. We performed this procedure in two patients. Operative time was 326 and 370 min, respectively. Patients were discharged on postoperative days 9–12 without postoperative complications. Discussion: Duodenal tumors are found increasingly often because of developments in endoscopic technology and techniques; therefore, establishing safe surgical procedures for duodenal tumor excision is imperative. Our surgical approach was simple and safe procedure. Conclusion: Laparoscopic pancreas-sparing distal duodenectomy with a bilateral approach is a useful approach without wide mobilization of duodenum.